Jammin’ the Blues: Experiencing the “Good Life” - Debrot, Ruth A. (Frontiers in Psychology, 2021)
Abstract The purpose of this study was to examine the characteristics, attitudes, and perceptions of older musicians who participated regularly in a local blues jam. Six core dimensions of eudaimonic well-being and their conceptual foundations provided a framework for examining the ways, if any, that music-making might contribute to subjective well-being during the lifespan of an individual. The following research questions guided this investigation; (1) In what ways do culture, affordances, and engagement with music influence the lives of older adult blues/rock musicians who participate in a local blues jam? (2) What implications for subjective well-being with regard to lifelong music learning, if any, might be used to inform music education practices? Interviews and observations over a 2-month period provided data for understanding how lived experiences impacted personal well-being, and musical growth and development, over time. Findings indicated that collaborative, participatory endeavors can provide a social and psychological sense of satisfaction among older adults. Implications for music education include the cultivation of participatory, self-directed, informal music classrooms that include technology-based, popular music pedagogies, in order to encourage life-long music learning and participation.